Study on evolution of NR duplex operation - Ting KE; Xinghua SONG; Fei WANG; Zhiheng GUO; Tuo YANG; Chunxia GUO; Chengcheng HAN; Yunfeng LIU; Zhenyu LI (Dianxin kexue)
Subband non-overlapping full duplex (SBFD) at gNB side within a conventional TDD band was considered as a key feature of 5G-Advanced to fulfill the challenging requirements of low latency and high uplink throughput emerging in vertical industry and industrial internet.Meanwhile, gNB-to-gNB cross-link interference handling needed to be enhanced to enable different TDD configurations for both public network (Macro) and vertical network (Micro) applied in the same frequency band.With a thorough analysis on the interference characteristic in the potential deployment scenarios for both different TDD configurations and subband non-overlapping full duplex, various feasible interference handling schemes to fulfill the challenging deployment requirements for vertical industry and industrial internet were presented, and the feasibility of above duplex enhancement schemes was checked via link budget, simulation and proof-of-concept prototype.